Eksperimentalna uporaba kvantitativne elektroencefalografije pri analizi (literarnega) branja - Bon, Jurij (Slavistična revija, 2016)
The article is the second part of the survey on the use of the electroencephalographic (EEG) methods in the analysis of (literary) reading. Contrary to prevalent cognitive theories, which propose that the brain works according to the principle of specialized modular processes (the so-called modular model), alternative theories supported by emerging brain imaging data presuppose the existence and simultaneous interactions of a number of different representations, supported and maintained by distributed neuronal mechanisms (the so-called activated states model). This question can also be approached by using the time-frequency analysis of EEG data, which, compared to the classic ERP analysis, allows an insight into parallel processing by dividing time course of oscillatory electrical activity of the brain into frequency bands. Individual frequency bands are considered to be important for various aspects of cognitive mechanisms, which are also the basis of language processing in reading. In this context, the most interesting rapid brain rhythms are beta and gamma and the most interesting slow rhythm is theta.
Keywords: activated states models; brain rhythms; branje; cognitive neuroscience; elektroencefalografija; empirical literary studies; empirična literarna znanost; jezikovna obdelava; kognitivna nevroznanost; language processing; možganski ritmi; reading; silent reading; tiho branje; time-frequency analyisis